Limit State Response of Composite Columns and Beam-Columns Part II: Application of Design Provisions for the 2005 AISC Specification - Leon, Roberto T.; Hajjar, Jerome F. (Engineering Journal, 2008)
The 2005 AISC Specification for Structural Steel Buildings contains substantial changes to the design provisions for composite members and composite columns in particular. This paper presents detailed and cross-sectional analysis and design examples for composite columns illustrating the new provisions. The paper focuses on providing a detailed description of the development of simplified equations for the creation of interaction curves for composite beam-columns. This is the second part of a two-part paper; the first paper contains detailed discussion of the development of the new provisions.